ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል አንድ - International Livestock Research Institute (International Livestock Research Institute, 2025)
The first episode of ‘Gebeta’ in 2025, which aired on Debre Birhan Fana FM 94.0, featured an interview with ILRI scientists Kindu Mekonnen and Million Gebreyes. They shared insights on ongoing livestock feed and forage innovations in Ethiopia, their objectives, and the successes of these interventions in the country. This radio program series is produced by the CGIAR Sustainable Farming and Scaling for Impact (S4I) programs, and the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) and Technologies for African Agricultural Transformation (TAAT) projects.